2022
DOI: 10.1038/s41467-022-34727-2
|View full text |Cite
|
Sign up to set email alerts
|

Engineering superconducting qubits to reduce quasiparticles and charge noise

Abstract: Identifying, quantifying, and suppressing decoherence mechanisms in qubits are important steps towards the goal of engineering a quantum computer or simulator. Superconducting circuits offer flexibility in qubit design; however, their performance is adversely affected by quasiparticles (broken Cooper pairs). Developing a quasiparticle mitigation strategy compatible with scalable, high-coherence devices is therefore highly desirable. Here we experimentally demonstrate how to control quasiparticle generation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Such a redesign will concentrate the power emitted by the SFQ driver below the aluminum gap edge, so that QP generation is not possible. The qubit and the SFQqubit coupler could also be modified to suppress their antenna coupling to free space at frequencies just above the aluminum gap [50,51,54]. To protect the qubit from any residual nonequilibrium QPs, appropriate superconductor gap engineering [31,[57][58][59][60] could be harnessed to promote the rapid outflow of QPs from the qubit junction and to prevent the inflow to the junction of QPs from remote parts of the qubit circuit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a redesign will concentrate the power emitted by the SFQ driver below the aluminum gap edge, so that QP generation is not possible. The qubit and the SFQqubit coupler could also be modified to suppress their antenna coupling to free space at frequencies just above the aluminum gap [50,51,54]. To protect the qubit from any residual nonequilibrium QPs, appropriate superconductor gap engineering [31,[57][58][59][60] could be harnessed to promote the rapid outflow of QPs from the qubit junction and to prevent the inflow to the junction of QPs from remote parts of the qubit circuit.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that absorption of pairbreaking photons is a dominant source of QP poisoning in Josephson devices [51,[53][54][55]. For typical geometries, the superconducting qubit structure forms a resonant antenna that provides an efficient power match from free space to the high-impedance Josephson junction at mmwave frequencies [50].…”
Section: Antenna Coupling Of the Sfq Transient To The Qubitmentioning
confidence: 99%
“…There are many mechanisms affecting qubit lifetime, [2,3] including losses induced by two-level system (TLS), [2,4,5] Purcell effect, [6,7] and quasiparticles (QP). [8,9] The energy relaxation rate Γ 1 is given by…”
Section: Introductionmentioning
confidence: 99%
“…Several mitigation strategies have been proposed to combat these ionizing impact events at the level of the quantum device, such as the direct trapping of quasiparticles through gap engineering [17][18][19][20] as well as impeding the propagation of phonons by substrate modification [21][22][23][24]. A complementary approach is the use of so-called phonon traps [15,23,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%